Filsafat Sains Islam dalam Perspektif Ontologi, Epistemologi, dan Aksiologi: Studi Literatur - Timur Tumanggor; Hasan Bakti Nasution (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study aims to examine Islamic philosophy of science from the perspectives of ontology, epistemology, and axiology through a comprehensive and critical literature study approach. The research method used is qualitative library research, analyzing relevant books and scientific articles, both classical and contemporary. The results of the study indicate that Islamic philosophy of science views reality as a meaningful and purposeful unity, integrating revelation, reason, and empirical experience as sources of knowledge, and situating science within a framework of ethical values, justice, and welfare. However, this study also found a gap between the discourse of Islamic philosophy of science and contemporary scientific practice, particularly in higher education and scientific research in the Muslim world. This study emphasizes that the integration of ontology, epistemology, and axiology is a primary prerequisite for realizing an Islamic scientific paradigm that is holistic, reflective, and relevant to the challenges of modern science